2018
DOI: 10.3389/fphys.2018.00244
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Protects Against Tourniquet-Induced Acute Ischemia-Reperfusion Injury in Mouse Hindlimb

Abstract: Extremity injuries with hemorrhage have been a significant cause of death in civilian medicine and on the battlefield. The use of a tourniquet as an intervention is necessary for treatment to an injured limb; however, the tourniquet and subsequent release results in serious acute ischemia-reperfusion (IR) injury in the skeletal muscle and neuromuscular junction (NMJ). Much evidence demonstrates that inflammation is an important factor to cause acute IR injury. To find effective therapeutic interventions for to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…It has been reported that ischemic preconditioning [ 9 ], ischemic postconditioning [ 21 ], controlled reperfusion [ 22 ], hypothermia [ 23 ], light-emitting diode therapy [ 24 ] and some other physical therapies can relieve skeletal I/R injury [ 25 ]. In addition, several agents, such as dexamethasone [ 10 ], curcumin [ 26 ], salvianolic acid [ 8 ], silibinin [ 27 ], simvastatin [ 28 ], cyclosporine A [ 29 ], hydrogen-rich saline [ 30 ] and lipoxin A4 [ 4 ], have been shown to be effective in attenuating skeletal I/R injury. In cases of traumatic injuries in which I/R is not predictable and early intervention is desired, such strategies are not as relevant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that ischemic preconditioning [ 9 ], ischemic postconditioning [ 21 ], controlled reperfusion [ 22 ], hypothermia [ 23 ], light-emitting diode therapy [ 24 ] and some other physical therapies can relieve skeletal I/R injury [ 25 ]. In addition, several agents, such as dexamethasone [ 10 ], curcumin [ 26 ], salvianolic acid [ 8 ], silibinin [ 27 ], simvastatin [ 28 ], cyclosporine A [ 29 ], hydrogen-rich saline [ 30 ] and lipoxin A4 [ 4 ], have been shown to be effective in attenuating skeletal I/R injury. In cases of traumatic injuries in which I/R is not predictable and early intervention is desired, such strategies are not as relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Under oxidative stress or inflammatory response conditions, the MAPK and NF- κB pathways can be activated [ 10 ]. Recent studies have shown that in some I/R injury models, including the skeletal I/R injury model, the p38, ERK1/2, JNK and p65 pathways are active [ 4 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 While ischaemia often causes the initial insult, reperfusion leads to a second-hit, intense inflammatory response that can cause muscle apoptosis and necrosis in what has been termed the ischaemia-reperfusion (IR) injury. 3 Other causes of skeletal muscle IR injury include elective or emergent tourniquet use, acute or chronic compartment syndrome, and vascular injury requiring repair. 4 Preventing IR injury has been an area of interest in cardiology after myocardial infarction (MI) but has not been aggressively pursued in the orthopaedic realm.…”
Section: Historical Significancementioning
confidence: 99%
“…Reperfusion of the acute ischemic tissue triggers a potent production of reactive oxygen species (ROS) and cytokines, which promotes a proin ammatory state and subsequently increases lung vulnerability to further injury [1,4,7,8]. Although several treatment strategies have been proposed to attenuate the remote organ injury following tourniquet use, most of them were limited to animal experiments and no ideal treatment was proved to improve prognosis [9,10]. Therefore, to reinforce the anti-in ammatory response and endogenous protective effect would be a new strategy for improving the prognosis.…”
Section: Introductionmentioning
confidence: 99%